What ended the great depression? Reevaluating the role of fiscal policy - Nathan Perry; Matías Vernengo (Levy Economics Institute of Bard College, 2011)
Conventional wisdom contends that fiscal policy was of secondary importance to the economic recovery in the 1930s. The recovery is then connected to monetary policy that allowed non-sterilized gold inflows to increase the money supply. Often, this is shown by measuring the fiscal multipliers, and demonstrating that they were relatively small. This paper shows that problems with the conventional measures of fiscal multipliers in the 1930s may have created an incorrect consensus on the irrelevance of fiscal policy. The rehabilitation of fiscal policy is seen as a necessary step in the reinterpretation of the positive role of New Deal policies for the recovery.
Keywords: E62; E63; N12; 330; fiscal policy; Great Depression